(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article is devoted to Hazrat Alisher Navoi’s ghazals on the topic of education. The research work analyzes Navoi’s views on education. The ideas that Navoi’s ghazals, written in the spirit of the pandnama, lead a person to high perfection are recognized.